Desenvolvimento de Software para Videolaringoscópio Assistivo de Baixo Custo Aplicado ao Treinamento e Ensino de Laringoscopia - Alcântara, Tiago G. R. M. de; Souza, Bruno P. de; Travassos, Guilherme H. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2025: Anais Estendidos do XXXI Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2025.16355, 2025)
This work presents the development of a software system for an assistive technology video laryngoscope, integrating Internet of Things (IoT) principles and web technologies to enable real-time video transmission and remote interaction via mobile devices. The proposal aims to support healthcare professionals in their training and education for proper laryngoscope handling, addressing the shortage of practitioners adequately trained in endotracheal intubation. By combining hardware and software components in a client–server architecture—using an ESP32-CAM board, FSR (Force Sensing Resistor) sensors, and contemporary web technologies—the system offers a low-cost and accessible alternative, particularly suited for public educational institutions. With an estimated cost of R$195.00, compared to similar equipment exceeding R$10,000.00, the solution stands out as a viable, innovative, and scalable approach for healthcare education and clinical simulation. Initial system evaluations demonstrated the feasibility of building the video laryngoscope and confirmed its ability to connect, transmit, and receive data effectively.